A Novel Perchlorinated Cyclohexasilane Salt with Intramolecular Hydrogen Bonding and its Application in the Synthesis of Cyclohexasilane - Liu, Zhikun; Yang, Xingjie; Chen, Ping (Current Organic Chemistry, 2026)
Ionic compounds of tetradecachlorocyclohexasilane, a critical precursor for cyclohexasilane and its derivatives, have been synthesized using various methods. However, these approaches are often hindered by low yields, high costs, and environmental concerns. In this study, a novel perchlorinated cyclohexasilane salt, [(i-Pr2EtNH)2Cl+]2[Si6Cl142-], was synthesized by the cyclization of trichlorohydrosilanes with diisopropylethylamine. The compound differs from previously reported six-membered silicocyclic ionic compounds. Notably, the chlorine atom in the cation does not form a direct covalent bond with the surrounding atoms. Instead, it forms a hydrogen bond, a feature not observed in the cationic components of other tetradecachlorocyclohexasilane dianion compounds. The structure was confirmed through single-crystal X-ray diffraction, NMR spectroscopy, and elemental analysis. The perchlorinated cyclohexasilane salt was subsequently reduced to cyclohexasilane using metal hydrides, achieving an overall yield of 44.2% across the two-step process. This method offers several advantages, including cost-effectiveness, high yields, simple purification, and mild reaction conditions. The results demonstrate the utility of this approach for synthesizing cyclohexasilane and advancing its applications as feedstocks for silicon deposition in the development of micro- and nano-silicon materials.
Keywords: Perchlorinated cyclohexasilane salt